2023
DOI: 10.1126/sciadv.adi3902
|View full text |Cite
|
Sign up to set email alerts
|

Association between frailty and depression: A bidirectional Mendelian randomization study

Ming-Gang Deng,
Fang Liu,
Yuehui Liang
et al.

Abstract: Frailty and depression were linked in observational studies, but the causality remains ambiguous. We intended to explore it using Mendelian randomization (MR). We obtained frailty genome-wide association study (GWAS) data from UK Biobank and TwinGen meta-analysis, and depression GWAS data from Psychiatric Genomics Consortium (PGC) and FinnGen (respectively recorded as PD and FD). We performed univariable and multivariable-adjusted MR with adjustments for body mass index (BMI) and physical activity (PA). Frailt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Speed et al have shown that BMI is a causal risk factor for depression, but found no significant evidence that depression causes increased BMI [ 31 ]. These findings are consistent with other studies reporting that higher BMI causally increases the risk of depression, but that the inverse relation does not hold [ 32 , 33 ]. Obesity triggers dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, causing excessive cortisol production.…”
Section: Discussionsupporting
confidence: 92%
“…Speed et al have shown that BMI is a causal risk factor for depression, but found no significant evidence that depression causes increased BMI [ 31 ]. These findings are consistent with other studies reporting that higher BMI causally increases the risk of depression, but that the inverse relation does not hold [ 32 , 33 ]. Obesity triggers dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, causing excessive cortisol production.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the Steiger directionality test validates the effectiveness of the vast majority of forward causality. Because the methodology of MR is inherently less susceptible to the spurious reverse causality, bidirectional MR can indeed suggest that two phenotypes drive each other, and this situation does not affect the validity of forward causality 64 . Second, there is mild horizontal pleiotropy in the MR analysis results for SHBG and HDL-C (p = 0.02), which could potentially violate assumption II and III, leading to inaccurate causal estimates 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest a bidirectional causal relationship between frailty and depression from a genetic perspective (Deng et al, 2023).…”
Section: Backg Rou N Dmentioning
confidence: 99%